Pengaruh Jumlah Kunjungan Wisatawan, Lama Tinggal dan Pengeluaran Wisatawan Mancanegara Terhadap Pendapatan Sektor Perdagangan, Hotel dan Restoran (PHR) Provinsi Bali Tahun 2000-2012 - Putra Wijaya, Ida Bagus; Setyadhi Mustika, Made Dwi (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 3, No. 4, April 2014 (pp. 124-172), 2014)
Tourism is an important industry for the economy of Bali province that does not have natural resources such as oil and gas , forest products and manufacturing industries. This study examines the effect of the number of tourist arrivals , average length of stay of foreign tourists, the average foreign tourist spending and revenue trade hotels and restaurants (PHR) of Bali Province in 2000-2012 , u sing secondary data from the Bali Provincial Tourism Office and the BPS Bali Province. This study used path analysis (path analysis) with the results of equations simultaneously substructure 1 is the number of tourist arrivals and average length of stay significantly influence the average foreign tourist spending partially but the average length of stay of foreign tourists do not affect the average expenditure of foreign tourists. Substructure Equation 2 is simultaneously the number of tourist arrivals, average length of stay of foreign tourists and the average spending foreign tourists have a effect on the income PHR sector, only the average length of stay is no partial effect on PHR sector . Normal 0 false false false IN X-NONE X-NONE
Keywords: Tourist arrivals; length of stay; expenditure; PHR.